2016
DOI: 10.1103/physrevb.94.094309
|View full text |Cite
|
Sign up to set email alerts
|

Robust solidXe129longitudinal relaxation times

Abstract: We find that if solid xenon is formed from liquid xenon, denoted "ice", there is a 10% increase of 129 Xe longitudinal relaxation T1 time (taken at 77 K and 2 Tesla) over a trickle-freeze formation, denoted "snow". Forming xenon ice also gives unprecedented reproducibility of 129 Xe T1 measurements across a range of 77-150 K. This temperature dependence roughly follows the theory of spin-rotation mediated by Raman scattering of harmonic phonons (SRRS), though it results in a smaller-than-predicted spin-rotatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“… 17 would allow transporting the solid sample to a remote location prior to melting. It is noteworthy that it has also been demonstrated that hyperpolarized 129 Xe can be stored for an extended period of time and transported in the solid form at cryogenic temperature 28 29 .…”
Section: Resultsmentioning
confidence: 99%
“… 17 would allow transporting the solid sample to a remote location prior to melting. It is noteworthy that it has also been demonstrated that hyperpolarized 129 Xe can be stored for an extended period of time and transported in the solid form at cryogenic temperature 28 29 .…”
Section: Resultsmentioning
confidence: 99%
“…One focus of this review is on the measures that have been taken to circumvent the challenges presented by the transient nature of spin hyperpolarization. Examples include generating hyperpolarization in situ (i.e., at the point of detection) to avoid relaxation losses during transport, , choosing/changing the state of matter to take advantage of slower relaxation, for example, in cryogenically cooled solids, , transferring the hyperpolarization to slower-relaxing lower-γ nuclei with the possibility to transfer back to a high-γ nucleus for a more sensitive readout, , and temporarily storing hyperpolarization in long-lived spin states. , …”
Section: Spin Hyperpolarization - Principles Sources and Source-to-ta...mentioning
confidence: 99%
“…The improved accumulation rates and absolute polarization achieved with the richer 129 Xe blend highlight the importance of solid-state T 1 relaxation in the 129 Xe snow as demonstrated in Figure 5, where 1000 mL accumulations were simulated for 129 Xe blends of f = 1%, 2% and 3% as a function of accumulation time. Here, two T 1 snow times are considered: 150 minutes, reported by M. E. Limes et al [21] for 129 Xe in 77 K polycrystalline snow, and the shorter 84 minutes in 129 Xe snow extracted from the experimental data in this work. Unsurprisingly, deviations in the behavior predicted for the two relaxation times are minimal for all three gas blends at low accumulation times (20 minutes or less).…”
Section: Resultsmentioning
confidence: 99%
“…One major motivation for cryogenic accumulation stemmed from Driehuys, et al [20], where the T 1 relaxation time in crystalline 'ice' 129 Xe was thought to be very long (180 minutes) at liquid N 2 temp (77 K) [52,53]. However, M. E. Limes et al [21] showed that the T 1 relaxation time in polycrystalline 'snow' at 2.0 T is 30 minutes shorter than in crystalline ice, suggesting that losses during cryogenic accumulation may be non-trivial. Norquay, et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation